Pig management in the Neolithic Near East and East Asia clarified with isotope analyses of bulk collagen and amino acids - Itahashi, Yu (Frontiers in Ecology and Evolution, 2022)
The chemical analysis of animal bones from ancient sites has become a common approach in archaeological research investigating animal utilization and domestication by past humans. Although several chemical indicators have been used to determine pig management practices in ancient societies, one indicator that can clarify human-animal relationships in the early stages of domestication is the change in the animal's diet from its wild diet, which can be detected using isotope analysis of its bones. Omnivores, such as boars, are assumed to have shared foods with humans as their interaction increased, and a shift in the isotopic (carbon and nitrogen) compositions of their bone collagen toward humans are considered evidence of domestication. This approach has found evidence of early-stage pig management with human leftovers and dung in prehistoric East Asia, including in Neolithic China and Japan. However, in the Near East, one of the origins of animal domestication, even individual animals considered to be domestic pigs according to zooarchaeological data (such as morphological characteristics and mortality patterns) display isotopic compositions of bulk collagen that differ from those of humans but are close to those of herbivores. This result indicates that these pigs were fed special foods, such as legumes, rather than human leftovers or dung. However, the carbon and nitrogen isotopic compositions of the bulk collagen of herbivores found at the same sites showed huge variations, so the interpretation of the pigs' diet is consequently unclear. In this study, a compound-specific nitrogen isotope analysis was used to clarify the pig diet and management strategies unique to the Neolithic Near East, Turkey, and Syria, together with a carbon and nitrogen isotope analysis of bulk collagen. This study examines the diversity of pig management techniques in early agricultural societies and their relationship with the availability of other domestic animals and farming practices.